Foreword from Editor - 12th Edition - Andri Yatmo, Yandi (ASEAN Journal of Community Engagement, 2022)
This edition of AJCE focuses on three main objectives of community engagements, running under the theme of literacy, creative innovation, and resilience. Covering these objectives, this edition consists of three research articles and five case-based articles written by authors from multi-nationalities. These authors' expertise spans across fields and industries, from communications, journalism, nursing, and economics; demonstrating various means of engaging with society informed by their respective backgrounds.